Strategi Kampanye Digital Efektif Berlandaskan Nilai-Nilai Pancasila - Ahmad Muhamad Mustain Nasoha; Ashfiya Nur Atqiya; Almaidah Yogi Mahanani; Oktaviana Nurul Amalia; Ulfah Hamidah (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Political communication based on Pancasila values serves as a crucial foundation for developing ethical and effective digital campaign strategies in Indonesia. The advancement of technology has transformed political campaigns from face-to-face interactions into digital engagements through social media, websites, and messaging applications. This study aims to analyze the application of Pancasila principles in digital political campaigns and evaluate their effectiveness in fostering ethical, people-centered political communication. Using a qualitative approach, this research employs content analysis of digital campaign materials from various political parties. The findings indicate that campaigns emphasizing values such as unity, humanity, social justice, and deliberation can enhance public participation, particularly among younger voters. Key success factors include information transparency, open dialogue, polite language use, and the provision of objective political education. Pancasila-based digital campaigns also help mitigate social polarization and strengthen public trust in the democratic process. Therefore, this model of political communication is worth adopting as a campaign approach that not only seeks electoral support but also reinforces a substantial and dignified democracy.